Focusing on Eye Contact: Interpersonal Communication among Students at EasternMediterranean University - Gounaili, Kamin (Eastern Mediterranean University (EMU), 2011)
This study aims to find the factors that affect eye contact decoding which gives different meanings to different people. This research aims to find out about different elements of eye contact in personal relationships between people like partners, married couples, friends and strangers. Eye contact is the only common language in the world and feature of non-verbal communication which is a branch of interpersonal communication. It is as old as humanity and common in our everyday lives but is hardly researched in communication studies. I set out to shed light on difference in establishing and decoding eye contact with the opposite and the same sex in respect to culture, media and context where it takes places. Qualitative methodology has been chosen and carried out among the students at the Eastern Mediterranean University in the Turkish Republic of Northern Cyprus. Data were collected from three different levels. The first one is semi-structured interviews with students from twenty one to thirty years old. The participants are from different countries like Albania, Turkey, Iran, Turkish Republic of Northern Cyprus, Nigeria and Cameroon. The second method is focus group interviews.Ten people participated in these sessions: Five of them are males and five are females, from nineteen to twenty nine years old and all these students are from different cities of Turkey. The last one is field notes that are based on the notes the researcher on the subject. The data were analyzed and common answers are triangulated.The results show that eye contact is an important language of interpersonal communication. It can communicate a variety of attitudes such as anger, love, sadness, happiness as facial expression in different situations. On the whole, from both research that we conducted with students of Eastern Mediterranean University and field notes the researcher kept, how to decode the many possible elements and understanding the discourses of eye contact are closely are tied to cultural, ethnic, gender, relationship, media, situation and other factors. Also the meaning of eye contact that is created can be totally different from each other.
Master of Arts in Communication and Media Studies. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Communication, Dept. of Communication and Media Studies, 2011. Supervisor: Assist. Prof. Dr. Bahire Efe Özad.
Keywords: Communication and Media Studies; Interpersonal communication - Students - Eastern Mediterranean University - Cyprus, North; Social psychology - Students - Eastern Mediterranean University; Eye Contact - Communication - Non-Verbal Communication - Interpersonal Communication